PELATIHAN PEMBUATAN MATERI PEMBELAJARAN DENGAN APLIKASI CANVA DI SMPN 1 MAJENE - Mayapada, Retno; Rahayu, Putri Indi; Hidayatullah, Muhammad (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2023)
The development of technology and information requires the world of education to always adjust to improve the quality of education. Improving educational performance will require information systems and information technology in the future, which not only serves as a supporting tool, but can be a very important tool to support the success of the world of education so that it can compete in the global world. Competency development is something that should be done by all professionals, including teachers. One of the challenges for teachers and developers of educational technology is to make innovative learning fun and not boring for students. Teacher competence in creating interesting and creative material affects teacher success in helping students achieve better learning outcomes. One of the uses of technology in learning is to use the Canva application. Training using the Canva application was carried out at SMPN 1 Majene. The participants who participated in this activity were 31 teachers. The purpose of the series of activities carried out is to provide training to teachers to use the Canva application. This training was also conducted based on observations, interviews, and surveys conducted with the school. The output of the series of activities carried out is that teachers gain new insights or refreshes about the Canva application so that they can use the Canva application to create interesting and creative learning materials.